Telling Women's Lives : Subject/Narrator/Reader/Text. - Long, Judy (Feminist Crosscurrents S., 1999)
For centuries, the "great man" format and masculine discourse of biography and autobiography have eclipsed women. If we accept this history, we remain ignorant of "Lady Sarashina," a Japanese woman of the Han period, whose book survives from the 11th century. We overlook Margaret Cavendish and Dame Julian, two early English autobiographers. And we fail to consider sufficiently slave narratives, oral histories, or lesbian "coming out" stories. Telling Women's Lives assesses existing traditions of autobiography and biography in search of a method capable of conveyin.